2016
DOI: 10.1002/ccd.26837
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison between three TAVR devices: ACURATE neo vs. CoreValve vs. SAPIEN XT. A single heart team experience in patients with severe aortic stenosis

Abstract: In a "real world" registry, ACT compared favorably against the well-studied SXT and MCV devices in both safety and efficacy. MCV implantation was associated with lower device success rates and higher rates of new permanent pacemaker implantation. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
(48 reference statements)
0
17
0
1
Order By: Relevance
“…4–7,21–36 Twenty studies (5670 patients) reported data on 30-day need for new PPI post-TAVI with a cumulative incidence of 7.7% (95% CI, 6.4–9.2%) (Figure 4). 4–7,21–36 In total, 20 studies (5478 patients) reported data on PVL, with a cumulative incidence of moderate/severe PVL of 4.3% (95% CI, 3.0–6.2%) (Figure 5). 4–7,21–36 Among 18 studies and 5617 patients with data on 30-day stroke rates, the cumulative incidence was 1.9% (95% CI, 1.6–2.3%) (Supplemental Figures, http://links.lww.com/CIR/A42).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4–7,21–36 Twenty studies (5670 patients) reported data on 30-day need for new PPI post-TAVI with a cumulative incidence of 7.7% (95% CI, 6.4–9.2%) (Figure 4). 4–7,21–36 In total, 20 studies (5478 patients) reported data on PVL, with a cumulative incidence of moderate/severe PVL of 4.3% (95% CI, 3.0–6.2%) (Figure 5). 4–7,21–36 Among 18 studies and 5617 patients with data on 30-day stroke rates, the cumulative incidence was 1.9% (95% CI, 1.6–2.3%) (Supplemental Figures, http://links.lww.com/CIR/A42).…”
Section: Resultsmentioning
confidence: 99%
“…4–7,21,23–36 The postdilatation incidence proportion, respectively, was 43.2% (95% CI, 37.9–48.6%) as evaluated from 19 studied (5808 patients) (Supplementary Figures, http://links.lww.com/CIR/A42). 4–7,21–36…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Полученные нами результаты демонстрируют высокий профиль клинической эффективности и безопасности использования биопротеза Acurate neo в течение 30 сут. после ТИАК, что соответствует опубликованным в зарубежной литературе данным [4][5][6].…”
Section: Discussionunclassified
“…[5][6][7] Generally, the Edwards SAPIEN 3 valve has shown favorable results in studies comparing clinical outcomes by valve type. 8,9 Researchers hypothesize that trauma to, and impingement upon, conduction bundles may be responsible for subsequent need for PPM after TAVR, given the location of the valve prosthesis near the aortic annulus and into the left ventricular outflow tract. 10 This is supported by the fact that several groups have uncovered preexisting right bundle branch block (RBBB) as a predictor of PPM.…”
Section: Introductionmentioning
confidence: 99%